The Influence of Service Quality and Price on Alfamart Consumer Loyalty with Customer Satisfaction As Mediation Variables - Herawaty, Mety Titin; Aprillia, Aprillia; Rahman, Aan; Rohimah, Luthfia; Taruna, Helmy Ivan; Styaningrum, Etik Dwi; Suleman, Dede (IJOSMAS, 2022)
This study aims to analyze the quality of service and price on consumer loyalty, with the variable customer satisfaction as a mediating variable. Data collected from 100 respondents of Alfamart minimarkets in Jakarta, Bogor, Depok, Tangerang and Bekasi. The distribution was carried out during December 2021, using the google form due to the pandemic conditions. The research method used is purposive sampling, namely people who shop at the Alfamart Minimarket in the last month and are willing to fill out the questionnaire that the researcher gave. The collected data were analyzed using Structural Equation Modeling with SmartPLS version 3.0 software. Hasil penelitian menunjukkan Service Quality has a positive and significant effect on Customer Satisfaction, Price has a positive and significant effect on Customer Satisfaction, Service Quality has a positive and significant effect on Customer Loyalty, Price has a no significant effect on Customer Loyalty, Customer Satisfaction has a no significant effect on Customer Loyalty, Customer satisfaction did not significantly mediate the service quality and price variables on consumer loyalty.